ANALISIS EKSISTENSI PENDIDIKAN AGAMA ISLAM (PAI) DI ERA SOCIETY 5.0 - Andryadi, A; Susanti, Weti; Saputra, Yahya; Yulianto, Y; Nurdin, Syafruddin; Zubaedi, Amin (Al’ulum Jurnal Pendidikan Islam, 2025)
Islamic Education (PAI) in the digital era and Society 5.0 faces significant challenges and opportunities due to the rapid development of technology and globalization. The concept of Society 5.0, which integrates the digital world with human life, raises challenges for Islamic education to remain relevant in responding to the challenges of the times. The purpose of this study is to examine the existence of Islamic Religious Education in the Era of Society 5.0 which is symbolized by human attachment to technological developments. This research uses a literature review approach. Data collection is done by tracing and analyzing various books, journals, magazines, and other library publications that are relevant to the research topic. The results of this study explain that Islamic education will continue to exist amid technological developments by continuing to adapt and be open to changing times. This article is expected to be able to provide spirit to Islamic Religious Education to continue to develop and utilize technology as a means of spreading religious values.